2014
DOI: 10.1002/hep.27057
|View full text |Cite
|
Sign up to set email alerts
|

Unresectable solitary hepatocellular carcinoma not amenable to radiofrequency ablation: Multicenter radiology-pathology correlation and survival of radiation segmentectomy

Abstract: Resection and radiofrequency ablation (RFA) are treatment options for hepatocellular carcinoma (HCC) <3 cm; there is interest in expanding the role of ablation to 3-5 cm. RFA is considered high-risk when the lesion is in close proximity to critical structures. Combining microcatheter technology and the localized emission properties of Y90, highly selective radioembolization is a possible alternative to RFA in such cases. We assessed the efficacy (response, radiology-pathology correlation, survival) of radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
182
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 254 publications
(191 citation statements)
references
References 33 publications
8
182
0
1
Order By: Relevance
“…Riaz et al have also previously described an intensification approach at a segmental level called radiation segmentectomy, producing good results (81% response rate; no clinical toxicity) and thus underlining the usefulness of the intensification concept (16,17). Recent results by means of radiation segmentectomy have demonstrated that the rate of complete histologic response was significantly higher for segments receiving a mean dose of 190 Gy or more (i.e., 66.6% for a segment dose $ 190 Gy, compared with only 25% for a segment dose , 190 Gy; P 5 0.03) (17). TDs were not provided in that study, thus rendering any direct comparison with our threshold TD of 205 Gy impossible.…”
Section: Discussionmentioning
confidence: 98%
“…Riaz et al have also previously described an intensification approach at a segmental level called radiation segmentectomy, producing good results (81% response rate; no clinical toxicity) and thus underlining the usefulness of the intensification concept (16,17). Recent results by means of radiation segmentectomy have demonstrated that the rate of complete histologic response was significantly higher for segments receiving a mean dose of 190 Gy or more (i.e., 66.6% for a segment dose $ 190 Gy, compared with only 25% for a segment dose , 190 Gy; P 5 0.03) (17). TDs were not provided in that study, thus rendering any direct comparison with our threshold TD of 205 Gy impossible.…”
Section: Discussionmentioning
confidence: 98%
“…A subanalysis of patients with HCC less than or equal to 3 cm was also performed, creating a cohort potentially comparable to radiofrequency ablation. Twenty-four of the 70 patients have been previously reported (9). In that prior study, the concept of RS was introduced and validated by using results from pathologic explants.…”
Section: Methodsmentioning
confidence: 99%
“…In their cohort, 33% of patients were amenable to liver transplantation after radiation segmentectomy. At pathologic examination of the native liver specimens, 100% necrosis and more than 90% necrosis were found in, respectively, 52% and 48% of patients (64). In HCC, the downstaging success rate with radioembolization is around 50% (range, 29%-67%), with a median time to downstaging of 3.1-4 mo (65).…”
Section: Clinical Outcome and Tumor Responsementioning
confidence: 99%